Application of TWIST MR angiography to aid successful central venous access in challenging patients: initial single-centre experience. Issue 11 (November 2016) - Armstrong, L.; Rodrigues, J.C.L.; Lawton, C.B.; Tyrell-Price, J.; Hamilton, M.C.K.; Manghat, N.E.
Abstract : Aim: To investigate whether time-resolved angiography with interleaved stochastic trajectories (TWIST) with GeneRalised Autocalibrating Partially Parallel Acquisitions (GRAPPA) parallel acquisition could be used successfully to non-invasively and efficiently image patients with more complex vascular access issues. Materials and methods: TWIST magnetic resonance angiography (MRA) in the GRAPPA algorithm was performed on 15 patients at our centre using the 1.5 T Siemens Magnetom Avanto MRI system. Images were interpreted by cardiac radiologists. Results: TWIST provided excellent dynamic imaging of the venous system, demonstrating venous occlusion, stenoses, and collaterals, as well as providing good anatomical detail. Conclusion: TWIST MRA enables successful identification of candidate sites for central/tunnelled line access, whilst diagnosing complications of long-term access such as venous thrombosis or congenital venous anomalies. Highlights: We assessed the use of MR angiography to assess central venous patency in patients with difficult access. Occlusive disease was identified in all patients. Successful intervention was performed on the basis of our findings.